Prenatal and Perinatal Risk Factors for Autism at National Children’s Hospital - Bhattarai, Arjun; KC, Nawaraj; Subedi, N; KC, Namrata; Bijukchhe, SM; Paudel, S (Journal of Gandaki Medical College-Nepal, 2018)
Background: Autism, or autism spectrum disorder, refers to a broad conditions characterized by challenges with social skills, repetitive behaviors, speech and nonverbal communication. Objectives: To determine the demographic profile of patients diagnosed with ASD, determine the significant prenatal and perinatal risk factors associated with ASD. Results: A total of 116 subjects were included in the study with 58 cases and 58 controls. They belong to the age ranging from 4 to 16 years old. Every case had a confirmed diagnosis of autism at NCH. There was a significant association noted between neonatal jaundice, nulliparity (OR=2.38; 95% CI, 0.85-6.8) and family history of autism (OR=5.30; 95% CI, 1.29-25.1) with ASD. Exposure to x-ray, medical problems, medicine intake and maternal complications during pregnancy were not significantly associated with ASD with OR 0.74; 95% CI, (0.12-4.15), OR 1.00; 95% CI (0.38-2.61), OR1.49; 95% CI, (0.63-3.53), and OR 1.27; 95% CI, (0.28-6.05), respectively. Conclusion: The current study indicates that the only significant predictor of ASD is a family history of autism. However, neonatal jaundice, maternal age of >40 years old, smoking during pregnancy and nulliparity showed a trend towards being risk factors for ASD. None of the other prenatal and perinatal characteristics significantly predicts ASD.